2014
DOI: 10.4239/wjd.v5.i6.835
|View full text |Cite
|
Sign up to set email alerts
|

Risks of rapid decline renal function in patients with type 2 diabetes

Abstract: Progressive rising population of diabetes and related nephropathy, namely, diabetic kidney disease and associated end stage renal disease has become a major global public health issue. Results of observational studies indicate that most diabetic kidney disease progresses over decades; however, certain diabetes patients display a rapid decline in renal function, which may lead to renal failure within months. Although the definition of rapid renal function decline remained speculative, in general, it is defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 116 publications
3
43
0
2
Order By: Relevance
“…The evidence that eGFR has a U-shaped association with mortality, including diabetes, questions the validity of studies which have assessed the prognostic significance of renal disease in statistical models assuming simple linearity or using categorisation that belies the complexity of the relationship. In addition, there is emerging evidence from general population (6) and diabetes (7,8) studies that a single eGFR does not identify patients in whom a subsequent relatively rapid decline from baseline also portends an adverse prognosis. This sub-group could explain the U-shaped relationship with death observed in studies utilising only baseline eGFR, since those patients with a relatively high initial eGFR could either progress quickly to renal impairment and death or maintain renal function with an associated favourable outcome.…”
mentioning
confidence: 99%
“…The evidence that eGFR has a U-shaped association with mortality, including diabetes, questions the validity of studies which have assessed the prognostic significance of renal disease in statistical models assuming simple linearity or using categorisation that belies the complexity of the relationship. In addition, there is emerging evidence from general population (6) and diabetes (7,8) studies that a single eGFR does not identify patients in whom a subsequent relatively rapid decline from baseline also portends an adverse prognosis. This sub-group could explain the U-shaped relationship with death observed in studies utilising only baseline eGFR, since those patients with a relatively high initial eGFR could either progress quickly to renal impairment and death or maintain renal function with an associated favourable outcome.…”
mentioning
confidence: 99%
“…The small changes in these renal parameters are consistent with progression of renal disease that might be anticipated in the study population. 21 Thus, there were no findings to suggest that omarigliptin treatment increases the risk of worsening renal dysfunction in this study population with RI.…”
Section: Discussionmentioning
confidence: 45%
“…[28] Zhou et al [29] recorded lower Vitamin D deficiency has recently been gaining acceptance as a risk factor for a decline in renal function in DM patients. [30] Furthermore, a meta-analysis demonstrated that vitamin D can ameliorate proteinuria and protect kidneys from injury in DM patients, independently from blood pressure and glucose reduction. [31] In light of these data, we looked for an association between vitamin D insufficiency and DN, but our results did not suggest this relationship with either microalbuminuria or macroalbuminuria.…”
Section: Discussionmentioning
confidence: 99%